Proceedings of the 2017 7th International Conference on Education, Management, Computer and Society (EMCS 2017) 2017
DOI: 10.2991/emcs-17.2017.189
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Multimodal Effects on ESP Listening Comprehension

Abstract: Abstract. This study inquires into the effect of multimodality on ESP listening comprehension by examining the students' English summaries of the audiovisual recording material that comprises 51 semantic units. The study objects are 120 randomly chosen pilot cadets, who are split evenly into 4 groups: 1 control group and 3 test groups. For each group, the material is presented three times but with a different combination of multimodal. Then by using SPSS (17.0), single factor ANOVA and Post Hoc multiple tests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
0
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 4 publications
1
0
0
Order By: Relevance
“…It is reported to increase the quality of ESP instruction and promote students' listening comprehension. It is also in line with the research conducted by Tao, Luo, and Zhao (2017) which aims to look into the effect of multimodality on ESP listening comprehension by examining the students' English summaries of the audiovisual recording materials. The result shows that proper use of multimodality can significantly improve students' listening comprehension.…”
Section: Introductionsupporting
confidence: 73%
“…It is reported to increase the quality of ESP instruction and promote students' listening comprehension. It is also in line with the research conducted by Tao, Luo, and Zhao (2017) which aims to look into the effect of multimodality on ESP listening comprehension by examining the students' English summaries of the audiovisual recording materials. The result shows that proper use of multimodality can significantly improve students' listening comprehension.…”
Section: Introductionsupporting
confidence: 73%
“…Advanced and multimodal media, which are technological advances in recent years, have been included in the listening process to enable listeners to enhance their listening comprehension through contextual cues (Cross, 2011) Many studies reported that multimodal media has a significant influence on second language (SL) or foreign (FL) Listening (Aldera, 2015;Keguruan dan Ilmu Pendidikan, Arfazul Ilmi, and Novita Dewi, 2022;Tao, Luo, and Zhao, 2017). For example, Ilmi and Dewi(Keguruan dan Ilmu Pendidikan et al, 2022) investigated English as a foreign language (EFL) learners' perceptions of the integration of multimodal information into English as a foreign language (EFL) classroom practices and reported that integrating multimodal information in the EFL learning process increased students' interest and engagement.…”
Section: Technology-assisted Listening Skillsmentioning
confidence: 99%
“…Meanwhile, Tao, Luo and Zhao (Tao et al, 2017) examined how multimodal information influences EFL students' listening comprehension, and modality congruence influences students' listening comprehension, especially when the visual modality matches the audio modality information.…”
Section: Technology-assisted Listening Skillsmentioning
confidence: 99%
See 1 more Smart Citation